Peran Madrasah Diniyah Dalam Mendukung Program Tahfidz di PPTQ Baitul ‘Abidin Darussalam Kalibeber Wonosobo - Intan Dina Aulifia; KH. Mukromin; Chairani Astina (Jurnal Mahasiswa Kreatif, 2024)
This thesis aims to: 1) To understand how the role of madrasah diniyah in supporting the tahfidz program at PPTQ Baitul 'Abidin Darussalam Wonosobo. 2) To find out how the tahfidz program at PPTQ Baitul 'Abidin Darussalam Wonosobo. 3) To find out the supporting and inhibiting factors of madrasah diniyah in supporting the tahfidz program at PPTQ Baitul 'Abidin Darussalam Wonosobo.This thesis uses a descriptive qualitative approach where the type of research is field research. Data collection techniques using observation, interview and documentation methods. The analysis technique used is data reduction, data presentation and conclusion drawing.The results showed that: 1) The tahfidz program at PPTQ Baitul 'Abidin Darussalam is reciting with 3x deposits for muroja’ah and 1x for ziyadah. In addition, there are also up and down juz and ngglondong programs that aim to strengthen memorization. PPTQ Baitul 'Abidin Darussalam Kalibeber Wonosobo also has a vision in the tahfidz program, namely to form a generation of huffadz who have Qur'anic souls and are proficient in general science (shari'at), so that in memorizing students it is recommended to be able to understand and practice the contents of the Al-Qur’an. 2) Equipping students with religious sciences (shari'at) that are salafiyah, where sciences like this are not taught in formal educational institutions. After being able to learn the sciences of sharia, students will understand better and find it easier to practice in everyday life. So that it can realize a Qur'an memorizer who can practice what is memorized so that it is more useful. 3) The supporting factors for the role of madrasah diniyah in supporting the tahfidz program at PPTQ Baitul 'Abidin Darussalam Kalibeber Wonosobo are curriculum management and a systematic teaching and learning process. While the obstacle is that some students are still boarding for the first time, making students less interested in learning and having difficulty understanding the lessons, of course it takes a long time to be able to adjust to the environment, besides that the infrastructure is still inadequate.